Isolation and identification of bacteria associated with diseased tilapia (Oreochromis niloticus Linneaus) from a Taal Lake fish cage - Ilagan, Y. A. (Animo Repository, 1999)
Diseased tilapia samples taken from a fish cage in Taal Lake were observed to have exhibited loss of scales, fin and gill defects, pop-eye and enlargement of stomach and abdominal dropsy symptoms. High bacterial counts (6.23-6.94 x 107 cfu/ml) were recorded from samples collected in August (dry season) relative to those in March (wet season) (3.89-4.08 x 107 cfu/ml). Thirty-two of 40 bacterial isolates were positive in pathogenicity test and caused mortality of healthy tilapia fingerlings. These pathogenic bacteria were identified as belonging to the following genera: Aeromonas, Pseudomonas, Flavobacterium, Edwardsiella, Vibrio, Enterobacter, Serratia, Alcaligenes and Bacillus based on cultural, morphological and physiological characterizations. Three isolates remained unidentified. Aeromonas, Pseudomonas, Edwardsiella, and Flavobacterium were found to be highly pathogenic in tilapia fingerlings. Majority of these pathogenic isolates were resistant to oxytetracycline, erythromycin, ampicillin, chloramphenicol and furazolidone. Minimal resistance was exhibited towards streptomycin. The observed pattern of antibiotic resistance may indicate critical farm medication practices which necessitate rationalization and permit of other nonresistance building therapeutic strategy.